Hubungan Antara Tingkat Konsumsi Energi, Protein dan Daya Beli Makanan dengan Status Gizi pada Remaja di SMP Negeri 2 Banjarbaru - Rusman Efendi; Rosihan Anwar; Sanna Riawu; STIKES Husada Borneo; Politeknik Kesehatan Banjarbaru (Jurnal Kesehatan Indonesia, 2014)
Adequacy of energy is influenced by several factors: age, gender, body size, physiological status, activity, thermic effect, and climate adaptation. For protein adequacy is influenced by factors age, sex, body size, physiological status, protein quality, energy consumption and adaptation. This study aimed to finding out the relationship of food consumerism and food nutrition status of teens school girl in junior school 2 Banjarbaru Year 2013. This research was an analytical cross sectional population. In this study population were male and female students of class VII and VIII. The sample in this study as many as 85 people. Analyzes performed tested these descriptive and statistical chi-square test. Results obtained no significant relationship between the level of food consumption and purchasing power with energy (p = 0,195). no significant relationship consumerism with protein (p = 0,437) of adolescent boys and girls in Junior High School Banjarbaru State 2. The expectation is to add the knowledge of the true nutritional status and apply it in everyday life, so as to have a good nutritional status.